Ionothermal Synthesis of Graphene-Based Hierarchically Porous Carbon for High-Energy Supercapacitors with Ionic Liquid Electrolyte. (1st July 2017) - Hao, Xiao-Feng; Yan, Yang; Gao, Li-Guo; Mu, Wen-Sheng; Hao, Ce
Abstract: Electrochemical double layer capacitors (EDLCs), storing charges by electrostatic attraction of electrolyte ions to the surface of charged electrodes, require an improved energy density to broaden their applications. Here a high-energy-density EDLC is reported by employing ionic liquids not only as the solvent for material synthesis but also as electrolyte. Graphene-based hierarchically porous carbon (GPC) are synthesized via ionothermal method, and exhibits high specific capacitance of 313 F g −1 and 212 F g −1 at a current density of 0.5 A g −1 in aqueous and ionic liquid electrolytes, respectively. The obtained GPC electrode retains about 94.2% of the initial capacitance after 10000 charge/discharge cycles at a current density of 2 A g −1 in aqueous electrolyte, strongly reflecting an excellent long-term cycling stability and rate capability of the electrode. A promoted energy density of 90.4 W h kg −1 can be obtained with neat ionic liquid electrolyte, which is about 8 times higher than that with aqueous electrolyte. The ionothermal process guarantees the acquisition of the hierarchical porous structure and high surface area, while the ionic liquid electrolyte assures a broader operating voltage, which both helps to increase the energy density of EDLCs.